Chapter Beach macro-litter monitoring on Monastir coastal sea (Tunisia): First Findings - Derouiche, Emna (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The macrolitter monitoring was investigated on 3 beaches on Monastir coastal (Palmier, Marina, Karaia) and on Kuriat Island during 4 seasons. The highest abundance and density of macrolitter were recorded on the beaches of Marina (13540 items/100m; 8.49 items m-2) and Karaia (6842 items/100m; 6.11 items m-2) during spring. According to Clean Coast Index, these 2 beaches were classified as extremely dirty whereas Kuriat Island was considered as very clean. Plastic items corresponded to the highest concentration of litter in studied sites and varying between 69% and 89% of total items. Cigarette butts are the most frequent type of debris